Visual Media Using in Subject Islamic Cultural History to Improve Learning Motivation of MTS Laboratorium Jambi Students - Asnawiyah Asnawiyah (INNOVATIO: Journal for Religious Innovation Studies, 2020)
The aim of this research is to observe visual media using in subject Islamic Cultural History or Sejarah Kebudayaan Islam (SKI) and to increase the learning motivation of MTs Laboratorium Jambi students. The research used Classroom Action Research (CAR) which was carried out in 2 cycles. The research subjects are 20 students of class VIII MTs Laboratorium Jambi. The data technique was carried out through observation and questionnaires. The data analysis technique is a qualitative descriptive analysis with a proportion formula. The results of the study are obtained from the teacher activity observation sheet in cycle 1 with an average proportion formula of 80.76% and in cycle II an increase in the average proportion value of 92.30% (very good) and the results of processing student motivation questionnaire data. in the subject of Islamic cultural history (SKI) using visual media in the first cycle, it reached 87% and in the second cycle increased 96.5% including in the very high category. Thus, the use of visual media can increase student motivation at MTs Laboratorium Jambi. Penelitian ini bertujuan mengetahui penggunaan media visual dalam mata pelajaran Sejarah Kebudayaan Islam (SKI) dan peningkatan motivasi belajar siswa MTs Laboratorium Jambi. Penelitian menggunakan metode Penelitian Tindakan Kelas (PTK) yang dilaksanakan sebanyak 2 siklus. Subjek penelitian adalah siswa kelas VIII MTs Laboratorium Jambi sebanyak 20 siswa. Teknik pengumpulan data dilakukan melalui observasi dan angket. Teknik analisis data adalah analisis deskriptif kualitatif dengan rumus persentase. Hasil penelitian yang diperoleh dari lembar observasi aktifitas guru pada siklus 1 dengan rumus persentase rata-rata 80,76%, dan pada siklus II mengalami peningkatan dengan nilai persentase rata-rata 92,30% (sangat baik) dan hasil dari pengolahan data angket motivasi siswa pada mata pelajaran sejarah kebudayaan Islam (SKI) dengan menggunakan media visual pada siklus I mencapai 87% dan pada siklus II meningkat meningkat 96,5% termasuk dalam katagori sangat tinggi. Dengan demikian, penggunaan media visual dapat meningkatkan motivasi belajar siswa pada MTs Laboratorium Jambi.